Effects of auditory rhythmic adaptation on lower limb joint mechanics during single-leg drop landings in individuals with functional ankle instability - Meng, Lingyue; Wang, Yubo; Wang, Zilong; Liu, Yongan; Tan, Yong; Zhang, Yue; Wei, Xinhui; Mao, Xiaokun; Zhang, Qiuxia (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study investigates the effects of auditory rhythmic adaptation on lower limb joint mechanics in individuals with Functional Ankle Instability (FAI) during drop landings, aiming to explore potential rehabilitation strategies.MethodsTwenty male FAI individuals performed single-leg drop landings under four rhythmic conditions (no rhythm, 60, 120, 180 bpm) after auditory rhythmic adaptation. Joint mechanics data were collected, and analyzed using two-way repeated measures ANOVA to examine the main effects and interaction effects of rhythm and limb condition. Rhythmic adaptation was assessed using time interval reproduction paradigm.ResultsThe ground reaction force (GRF), joint torque and joint stiffness were significantly influenced by side (p< 0.05). Hip and knee joint range of motion (RoM), lower limb and joint stiffness, joint torque were significantly affected by conditions (p< 0.05). Significant interaction effects were observed in joint stiffness and joint torque (p < 0.05).ConclusionRhythmic auditory adaptation modulates motor control strategies in individuals with FAI by influencing joint mechanics during drop landing. In particular, rhythmic adaptation at 120 bpm facilitates a proximal-dominant torque-redistribution strategy, characterized by higher hip and knee extension torques and increased ankle plantarflexion torque on the stable side, and increased hip extension torques on the stable side. These changes suggest the potential of 120 bpm to improve motor control and reduce injury risk.